School Literacy Movement Program and Its Impact on Students Reading Interest and Reading Comprehension Skills - Bellina Dewi Yulianti; Sri Sukasih (Jurnal Pendidikan dan Pengajaran, 2023)
This research was motivated by the low interest in reading and students' reading comprehension abilities. The School Literacy Movement was implemented as an effort to improve students' abilities in literacy. The School Literacy Program has the potential to increase students' reading interest and reading comprehension. The school literacy movement program often organizes various interesting activities such as writer's meetings, reading competitions, and book clubs. These activities can stimulate students' interest in reading and help them feel more connected to the world of literacy. This program focuses on teaching literacy skills, including reading comprehension. The aim of this research is to describe the implementation of the School Literacy Movement, the impact on reading interest, and the impact on fourth grade students' reading comprehension abilities. This research uses a qualitative method with a descriptive case study approach. The data collection techniques used were observation, interviews, questionnaires and documentation. The results of this research show that students have implemented the School Literacy Movement. Students' interest in reading has increased and their enthusiasm has increased. Students' reading comprehension abilities have also increased, it is known from tests on reading story texts and answering questions that students are able to understand the contents of the text, find the message of the story, and are able to summarize the story. In terms of reading comprehension, this program also integrates strategies and approaches supported by research to improve students' reading comprehension. Thus, the School Literacy Program can provide a strong foundation for the development of reading skills and better reading comprehension in students.